Factors Affecting the Role of Agricultural Extension Workers in the Development of Farmer Groups in West Koya Village, Jayapura City - Ngutra, Risky Novan (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to determine the factors that influence the role of agricultural extension workers in the development of farmer groups in Koya Barat Village. The method used was quantitative. The results showed that the role of agricultural extension officers in terms of the variable ability of motivation on average has been able to influence farmers in carrying out farming activities, correcting deficiencies and solving problems, providing information on assistance from the government, conducting training, and coaching from the center but less able to give awards to active members. For variable communication skills of farmer groups and farmers can be accepted both in the delivery of information, media, language used. For the variable of increasing farmers' knowledge in answering the types of superior seeds, good land processing, good types of fertilizers, how to control pests, smooth irrigation and irrigation until harvest. In the Farmer Income Variable, the presence of agricultural extension workers greatly affects the income of farmers through the information obtained in increasing the income of rice farmers.